2012
DOI: 10.1016/j.molbiopara.2011.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Role of expression site switching in the development of resistance to human Trypanosome Lytic Factor-1 in Trypanosoma brucei brucei

Abstract: Graphical abstractResistance to Trypanosome Lytic Factor-1 is largely independent of the expressed variant surface glycoprotein (VSG) gene.Highlight► Resistance to TLF-1 killing correlates with the loss of HpHbR expression. ► Changes in VSG expression were found to correlate with TLF-1 susceptibility. ► TLF-1 resistance in T. b. brucei is largely independent of the expressed VSG or ESAGs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Similar results were found in T. b. brucei , genetically very close to T. evansi , after 9 months of in vivo selection with NHS [153]. It was suggested that the reduction of ApoL-1 uptake might be associated with the low level of haptoglobin-hemoglobin receptor expression [154]. Whether T. evansi could develop any of the above strategies or others to resist ApoL-1 lysis remains uncertain.…”
Section: Zoonotic Aspectsmentioning
confidence: 53%
“…Similar results were found in T. b. brucei , genetically very close to T. evansi , after 9 months of in vivo selection with NHS [153]. It was suggested that the reduction of ApoL-1 uptake might be associated with the low level of haptoglobin-hemoglobin receptor expression [154]. Whether T. evansi could develop any of the above strategies or others to resist ApoL-1 lysis remains uncertain.…”
Section: Zoonotic Aspectsmentioning
confidence: 53%
“…Tbg has evolved independent mechanism(s) from Tbr for evading trypanolysis, one of which involves the haptoglobin-receptor, HbHpr [67,68]. Based on a survey of a small number of strains from the three subspecies for genetic variation in HbHpr , five fixed, non-synonymous amino acid substitutions were identified and hypothesized to be involved in evading the immunological response [69]. A genetic screen of HbHpr on a geographically more comprehensive sampling than the previous study, however, confirmed only one of these substitutions as fixed [70].…”
Section: Genetics Of Tsetse Populations Transmitting Tbr and Tbg Paramentioning
confidence: 99%